COMMUNITY ENGAGEMENT APPROACH IN THE CONSERVATION OF HERITAGE BUILDINGS IN TAIPING, MALAYSIA - KALSUM MOHD ISA, NOR; YAZID MOHD YUNOS, MOHD; HAIRY IBRAHIM, MOHD; MARZUKI, MAZDI (International Journal of Psychosocial Rehabilitation, 2020)
Community engagement has been revealed as a significant approach for heritage building conservation. This study aims to identify the extent of local community involvement in the community engagement efforts that had been undertaken to conserve heritage buildings in Taiping. It also seeks to determine the relationship between the perceived costs and benefits of the project and the level of involvement in decision-making. Besides, the relationship between the level of involvement and support of the community for the conservation of heritage buildings was also explored. The data collection methods used were questionnaire surveys and interviews. The questionnaire survey forms were distributed to 82 private building owners of gazetted heritage buildings in Taiping. Then, interviews were conducted among eight private building owners who are directly involved in the conservation of heritage buildings and an officer of the local authority for validation purposes. The findings obtained from the quantitative and qualitative analyses show that the level of community involvement in conserving heritage buildings was low as their opinions were not taken into account throughout the decision-making process. The community support was also low due to the losses incurred. Perceived benefits and perceived loss were found to have a significant relationship with the level of community involvement.